(untitled) (Journal of Cancer Research Updates, 2019)
Previously, we have reported the clinical significance of low-level radiation and also demonstrated the necessity to determine the threshold of radioactive levels in human beings. In the present study, apart from the direct exposure of alpha-ray with oral intake of radon222 dissolved water or inhaling radon222 gas, the experimental direct exposure to beta- and gamma-rays by wearing a cotton sack containing Samarskite with direct contact to skin for one month was conducted. The average of beta- and gamma-ray levels on the sack surface was approximately 400 μSV/hour. The biochemical laboratory tests involving immunological markers were assessed at the initial and end points. In this study, the partial but continual direct exposure of human body to beta- and gamma-rays for one month showed no harmful effects. There are no significant changes in any of the bio markers. Although this study is limited regarding the number of subjects, the procedure is quite simple; thus, the gathering data using this procedure by adjusting the types and levels of radioactivity would be helpful in finding out the accurate radioactive threshold in human beings.